ANALISIS PEMENUHAN STANDAR PROSES, STANDAR SARANA DAN PRASARANA DAN STANDAR PENGELOLAAN DI TAMAN KANAK–KANAK NEGERI PEMBINA KOTARAJA KOTA JAYAPURA - DIKI KURNIAWAN (Universitas Cenderawasih, 2020)
This study aims to analyze the extent to which the fulfillment of process standards, facilities and infrastructure standards, and management standards in Taman Kanak-Kanak Negeri Pembina Kotaraja. This research used a qualitative approach. The subjects of this study were the principal and teachers. Data collection through triangulation methods of observation, interviews and study documentation. Data analysis used through several stages including data reduction, data collection, data presentation and conclusions. The results of the study showed that (1) Taman Kanak-Kanak Negeri Pembina Kotaraja had met the process standard. This can be seen from the curriculum that has been created by the school, (2) Taman Kanak-Kanak Negeri Pembina Kotaraja has fulfilled some minimum standards of facilities and infrastructure standards. This is evidenced by the presence of educational toys that are complete enough to develop moral and religious values, motor skills, language, art, cognitive, social emotional, (3) Taman Kanak-Kanak Negeri Pembina Kotaraja has met management standards. This could be proven by the vision, mission, and goals of the school, the annual work plan made by the principal, the education calendar created by the school that refers to the Kota Jayapura Education calendar, the school organizational structure that contains positions, personnel and the flow of responsibilities and job descriptions and functions of each personnel in the school organizational structure. Keywords: Process standards, facilities and infrastructure standards, management standards